2016
DOI: 10.1007/s00268-016-3418-0
|View full text |Cite
|
Sign up to set email alerts
|

Survival After Emergency General Surgery: What can We Learn from Enhanced Recovery Programmes?

Abstract: Enhanced recovery after surgery (ERAS) has been adopted by many centres and across whole healthcare systems. The results have shown significant reductions in length of stay and postoperative complications. However, there has been very little change in these factors and mortality in emergency surgery. Can we learn from principles of ERAS for emergency abdominal surgery?Over the last 15 years, there has been a quiet revolution in the delivery of elective surgical care. The main drivers of these improvements are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 22 publications
0
17
0
1
Order By: Relevance
“…The lower number of trials and studies focusing on ERAS in ES clearly indicates that this is still a new area to explore (16). The studies we found were less homogeneous in focus, included all age groups and different pathologies.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…The lower number of trials and studies focusing on ERAS in ES clearly indicates that this is still a new area to explore (16). The studies we found were less homogeneous in focus, included all age groups and different pathologies.…”
Section: Discussionmentioning
confidence: 56%
“…Quiney et al (16) identified two studies that had applied a specific care pathway with some similarities to ERAS, for ES patients. Their application had resulted in considerably reduced mortality rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a consultant surgeon with wide experience in emergency surgery should be considered for performance of the intervention (3,11,12,16,27). Table 2 shows the recommended amendments to the World Health Organization Surgical Safety Checklist for elderly patients aged >75 years (27).…”
Section: Care Pathwaysmentioning
confidence: 99%
“…Studies have shown that MR protocols were not only feasible but also led to improvements in outcomes (3)(4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%